Morphological Characters of Squatter Settlements Analytical Study using Remote Sensing and GIS Techniques - ساطع عباس ســــناء; طارش عبـــد الـــرزاق; لطفي عبد الوهاب ميـــادة (Journal of Engineering and Sustainable Development, 2009)
The squatter settlements phenomenon is not considered as physical problem only, but in fact, it is a product of many reasons, which are categorized to political, economical and social one. In spite of their obvious similarities in their physical, social and legal characteristics globally, these settlements differ in their Morphological Characters by the effect of political, economic, social factors.The aims of this paper is to study the morphological characters of squatter settlements and their effect on urban fabric of the city, using remote sensing and geographic information systems based on modern software.The research problem was: (there is a gap in determining the morphological characters of the squatter settlements), while the main research hypothesis was (the morphological characteristics of squatter settlements have an effect in the consolidation process with the mother city).The research findings was the regular fabric of the squatter settlements showed a state of consolidation toward in side, with a great number of big islands , while the un regular scatter fabric showed a state of non-consolidation, with a great number of small islands.